Inhibitory Test of Papaya Leaf Extract (Carica papaya L.) against the Growth of Escherichia coli and Salmonella typhi Bacteria, and Review According to the Islamic Religion - Rifal Hendri Hermawan; Pratami Adityaningsari; Firman Arifandi (Junior Medical Journal, 2022)
Infectious diseases have been identified as a global health concern, as they contribute to morbidity and mortality and have a high transmission rate. Bacteria are known as the primary cause of infection problems. Extract of papaya leaf (Carica papaya L.) contains antibacterial compounds that inhibit the growth of E. coli and Salmonella typhi. This experiment evaluated the effectiveness of papaya leaf extract in inhibiting Escherichia coli and Salmonella typhi bacteria using MHA media. The papaya extract concentrations are 10%, 15%, 20%, 25%, 30%, and 100%, with chloramphenicol and aquadest serving as positive and negative controls, respectively. Escherichia coli and Salmonella typhi bacteria did not form an inhibition zone, indicating that the papaya leaf extract lacked antibacterial properties. According to the results of this study, Papaya leaf extract extracted with 99.9% methanol does not inhibit the growth of Escherichia coli and Salmonella typhi bacteria.